Polemik Penyatuatapan Peradilan Agama di Bawah Mahkamah Agung - Na'mah, Ulin (Asy-Syir'ah: Jurnal Ilmu Syari'ah dan Hukum, 2018)
Abstract: This article explores the debatable problems concerning with the unification of the Religious Courts under the auspices of the Supreme Court. The transfer of authority of the Religious Courts from the Ministry of Religion Affairs to the Supreme Court was deemed inappropriate and uprooted Religious Courts from its historical roots. Therefore, it is necessary to analyze the historical context of Religious Courts and its contemporary dynamics in the form of its unification under the justice system in Indonesia. This research concludes that the positioning of Religious Courts under the auspices of Ministry of Religious Affairs since the independence era was not an attempt to weaken its authority, but rather an effort to save Religious Courts from the threat of dismissal. Religious Court was posed to the threat of dismissal during the political turmoil in the early establishment of Indonesian state due to disputes over the determination of ideal form of the Indonesian state, between a secular state, a religious state, or a nation state. Thus, the transfer of the Relligious Courts from Ministry of Religious Affairs to the same roof with other courts under the auspices of the Supreme Court is not an effort to reduce the authority of the Religious Court or weaken existence. In fact, this unification has returned the Religious Court to its approriate position and eliminated the long-standing negative stigma against this institution.Abstrak: Artikel ini mengeksplorasi problematika penyatuatapan Pengadilan Agama (PA) di bawah Mahkamah Agung (MA) yang menyebabkan polemik. Pengalihan keberadaan PA dari Kementerian Agama ke MA dianggap tidak tepat dan membuat PA tercerabut dari akar historisnya. Oleh karena itu, perlu dianalisis lebih mendalam terkait sinkronisasi sejarah PA dan dinamika kontemporernya berupa unifikasi sistem peradilan di Indonesia. Penelitian ini menyimpulkan bahwa keberadaan PA di bawah Kementerian Agama yang terjadi sejak masa kemerdekaan bukanlah upaya pengebirian terhadap PA, melainkan merupakan sebuah bentuk usaha penyelamatan PA dari ancaman penghapusan. Ancaman penghapusan tersebut muncul ketika negara Indonesia masih belum stabil dikarenakan adanya perselisihan tentang diskursus bentuk negara Indonesia, antara negara sekuler, negara agama, dan nation state. Dengan demikian, keberadaan PA yang menjadi satu atap dengan peradilan lainnya di bawah MA bukanlah upaya mengurangi kewenangan atau melemahkan PA. Sebaliknya, penyatuatapan ini telah mengembalikan PA pada posisi seharusnya dan menghilangkan stigma negatif yang dituduhkan kepada PA selama ini.